Faktor-Faktor yang Mempengaruhi Kunjungan Antenatal Care Pada Masa Adaptasi Kebiasaan Baru Pandemi Covid-19 - Suryanti, Suryanti; Nurana, Sitti (Jurnal Kebidanan Malakbi, 2023)
Antenatal care is a health service provided to a pregnant woman starting from the beginning of pregnancy until the delivery process. During the COVID-19 pandemic, many policies were made related to maternal and neonatal health including restrictions on antenatal visits. This study used a quantitative survey method with a cross approach. sectional. The sample in this study used a total sampling technique. The results showed that the average age of the mothers who checked themselves was 20-35 years, high school education and most of them were primiparous mothers. In the bivariate analysis, there was a relationship between knowledge (p = 0.036), attitudes (p = 0.043), social and family factors (p = 0.035), and technology (p = 0.002) on antenatal care visits during the adaptation period for the new Covid-19 pandemic and There was no correlation between staff support (p=0.36), trust (p=0.6), service access (p=0.9), and economy (p=0.482) with antenatal care visits during the adaptation period to the new COVID-19 habit.